Nuclear localization of the tyrosine kinase BMX mediates VEGFR2 expression - Liu, Tingting (J Cell Mol Med, 2019)
Vascular endothelial growth factor receptors (VEGFRs) are major contributors to angiogenesis and lymphangiogenesis through the binding of VEGF ligands. We have previously shown that the bone marrow tyrosine kinase BMX is critical for inflammatory angiogenesis via its direct transactivation of VEGFR2. In the present study, we show that siRNA‐mediated silencing of BMX led to a significant decrease in the total levels of VEGFR2 mRNA and protein, without affecting their stability, in human endothelial cells (ECs). Interestingly, BMX was detected in the nuclei of ECs, and the SH3 domain of BMX was necessary for its nuclear localization. Luciferase assays showed a significant decrease in the Vegfr2 (kdr) gene promoter activity in ECs after BMX silencing, indicating that BMX is necessary for Vegfr2 transcription. In addition, we found that wild‐type BMX, but not a catalytic inactive mutant BMX‐K445R, promoted Vegfr2 promoter activity and VEGF‐induced EC migration and tube sprouting. Mechanistically, we show that the enhancement of Vegfr2 promoter activity by BMX was mediated by Sp1, a transcription factor critical for the Vegfr2 promoter. Loss of BMX significantly reduced Sp1 binding to the Vegfr2 promoter as assayed by chromatin immunoprecipitation assays. Wild‐type BMX, but not a kinase‐inactive form of BMX, associated with and potentially phosphorylated Sp1. Moreover, a nuclear‐targeted BMX (NLS‐BMX), but not cytoplasm‐localized form (NES‐BMX), bound to Sp1 and augmented VEGFR2 expression. In conclusion, we uncovered a novel function of nuclear‐localized BMX in regulating VEGFR2 expression and angiogenesis, suggesting that BMX is a therapeutic target for angiogenesis‐related diseases.